2019
DOI: 10.1002/cssc.201900900
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Active Monometallic Rhenium Catalysts for Selective Synthesis of 1,4‐Butanediol from 1,4‐Anhydroerythritol

Abstract: 1,4‐Butanediol can be produced from 1,4‐anhydroerythritol through the co‐catalysis of monometallic mixed catalysts (ReOx/CeO2+ReOx/C) in the one‐pot reduction with H2. The highest yield of 1,4‐butanediol was over 80 %, which is similar to the value obtained over ReOx–Au/CeO2+ReOx/C catalysts. Mixed catalysts of CeO2+ReOx/C showed almost the same performance, giving 89 % yield of 1,4‐butanediol. The reactivity trends of possible intermediates suggest that the reaction mechanism over ReOx/CeO2+ReOx/C is similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Differences in reactivity were observed for different Au loading methods; impregnation provided larger Au particles (≈12 nm) that were less able to activate H 2 activation compared with deposition‐precipitation which provided smaller particle sizes (≈3 nm) . A co‐catalytic monometallic system for the conversion of 1–4‐anhydroerythritol to 1,4‐butanediol was also reported and adopts a DODH/ isomerization/ hydration/ hydrogenation pathway (Scheme ) . ReO x /CeO 2 in combination with ReO x /C‐BP as catalysts provided 1,4‐butanediol in 89 % yield under an atmosphere of H 2 at 140 °C in dioxane.…”
Section: Heterogeneous Rhenium Catalystssupporting
confidence: 56%
“…Differences in reactivity were observed for different Au loading methods; impregnation provided larger Au particles (≈12 nm) that were less able to activate H 2 activation compared with deposition‐precipitation which provided smaller particle sizes (≈3 nm) . A co‐catalytic monometallic system for the conversion of 1–4‐anhydroerythritol to 1,4‐butanediol was also reported and adopts a DODH/ isomerization/ hydration/ hydrogenation pathway (Scheme ) . ReO x /CeO 2 in combination with ReO x /C‐BP as catalysts provided 1,4‐butanediol in 89 % yield under an atmosphere of H 2 at 140 °C in dioxane.…”
Section: Heterogeneous Rhenium Catalystssupporting
confidence: 56%
“…In the most recent research, we also found that the ReO x /CeO 2 catalyst without an Au promoter still could catalyze the DODH reaction in the presence of ReO x /C, enabling the reduction of 1,4-AHERY to 1,4-butanediol with the mixture of ReO x /CeO 2 and ReO x /C. 39 The Re species on carbon could activate H 2 like an Au promoter for the reduction of Re species on the CeO 2 surface which are the active sites in the conversion of 1,4-AHERY. Furthermore, CeO 2 without Re loading combined with ReO x /C even could convert 1,4-AHERY to 1,4-BuD, because the Re species on the carbon surface could move to CeO 2 surfaces to form ReO x /CeO 2 .…”
Section: Introductionmentioning
confidence: 74%
“…(10) As above, the optimized reaction conditions for 1,4-BuD production from 2,5-DHF were a temperature of 413 K and a H 2 pressure of 8 MPa, which were the same reaction conditions used in the reaction of 1,4-AHERY over the combination of ReO x -Au/CeO 2 (or ReO x /CeO 2 ) and ReO x /C catalysts as reported in our previous reports. 23,39 The optimized ReO x /WO 3 -ZrO 2 catalyst was applied to the reaction of 1,4-AHERY combined with the ReO x -Au/CeO 2 catalyst for DODH of 1,4-AHERY to 2,5-DHF under the standard reaction conditions. The time course of the reaction of 1,4-AHERY over the mixture of ReO x -Au/CeO 2 and ReO x / WO 3 -ZrO 2 is shown in Fig.…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample composition was also found to be excellent for low‐pressure DODH of methyl glycosides, in which protection of the stereostructure with high selectivity without protection of OH groups to the corresponding unsaturated sugar revealed this to be a powerful tool for biomass utilization . 1,4‐Butanediol can be derived from 1,4‐anhydroerythritol by using the monometallic mixed catalyst ReO x /CeO 2 +ReO x /C, which involves a rate‐determining step of forming 2,5‐dihydrofuran with reduced Re in the DODH step, in which the reducibility and mobility of Re species between supports plays a significant role …”
Section: Challenges and Scopementioning
confidence: 99%